Honesty Theory: French Pedagogical Project. Conversation Culture and Jansenism in France in XVII century - Botero Betancur, Constanza (Ciencias Sociales y Educación, 2015)
Honesty theory in France in XVII century became a cultural praxis in which women played the main role in function of men’s education. Conversation culture became a mundane tool of education. However, when the Jansenist religious doctrine became powerful among these ladies, mundane grace lost importance before divine grace
Keywords: conversation; mundane culture; Jansenism; grace; Honesty theory